Opportunities and Challenges of Digital Democracy in Indonesia - Darto Wahidin; Ichwani Siti Utami; Aida Restu Amalia; Alifia Aqida; Salwa Aidah (Badan Pembinaan Ideologi Pancasila, 2025)
The development of information and communication technology has brought significant benefitsto democratic life in Indonesia. However, challenges such as the spread of hoaxes, social polarization, and unequal access to technology hinder this potential. This study aims to describe the opportunities that exist in the implementation of digital democracy and analyze the challenges faced. The method used is a qualitative approach with data collection techniques through literature studies. The results show that opportunities in digital democracy in Indonesia include increased transparency, accessibility of information, and more active public participation in the decision-making process. However, significant challenges such as lack of digital literacy, cybersecurity risks, and inadequate regulations were also identified. This research confirms that the future of digital democracy in Indonesia relies heavily on collaboration between the government, society and the private sector. By creating an environment that supports active and responsible participation, it is hoped that digital democracy can develop in an inclusive and sustainable manner, providing tangible benefits to all levels of society